Modelowanie procesów usług bankowych z zastosowaniem narzędzi symulacji na przykładzie udzielania kredytu dla ludności - Łosiewicz, Ewa (Modelling of Bank Services Processes with the Application of the Simulation Tool on the Example of Griving Credits to the Population, 2005)
This paper presents banking processes modelling on the example of a mortgage product with the simulation's tool - a module of the business process management system - ADONIS. The process model of the mortgage product is created and analysed on the basis of the real data given by Polish banks.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 230-240